El abogado inocente. Reflexiones en torno a la Antropología y sus relaciones con el Derecho, a partir de una experiencia de campo con los ngäbes de Costa Rica - Argilés Marín, José Manuel (2023)
Based in the author’s fieldwork experience, carried out in the Ngäbe indigenous territories in Costa Rica, the article proposes an epistemological reflection about anthropological activity and its political consequences, as well as an exploration of some of the links between Law and Anthropology.